2015
DOI: 10.1111/nph.13309
|View full text |Cite
|
Sign up to set email alerts
|

A gain‐of‐function mutation of plastidic invertase alters nuclear gene expression with sucrose treatment partially via GENOMES UNCOUPLED1‐mediated signaling

Abstract: SummaryPlastid gene expression (PGE) is one of the signals that regulate the expression of photosynthesis-associated nuclear genes (PhANGs) via GENOMES UNCOUPLED1 (GUN1)-dependent retrograde signaling. We recently isolated Arabidopsis sugar-inducible cotyledon yellow-192 (sicy-192), a gain-of-function mutant of plastidic invertase, and showed that following the treatment of this mutant with sucrose, the expression of PhANGs as well as PGE decreased, suggesting that the sicy-192 mutation activates a PGE-evoked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…These observations are in line with the model suggesting that plastid gene transcription is controlled by retrograde signalling networks including sigma factors (SIG2, SIG6) and plastid encoded RNA polymerase (PEP) which might be crucial for proper plastid RNA transcription (Woodson et al, 2013). It seems that GUN1 activates PEP (Maruta et al, 2015) and a perturbed PEP activation in the gun1 mutant may prevent the upregulation of the plastid encoded genes in the treated gun1 mutant compared to the treated wild type.…”
Section: Discussionsupporting
confidence: 86%
“…These observations are in line with the model suggesting that plastid gene transcription is controlled by retrograde signalling networks including sigma factors (SIG2, SIG6) and plastid encoded RNA polymerase (PEP) which might be crucial for proper plastid RNA transcription (Woodson et al, 2013). It seems that GUN1 activates PEP (Maruta et al, 2015) and a perturbed PEP activation in the gun1 mutant may prevent the upregulation of the plastid encoded genes in the treated gun1 mutant compared to the treated wild type.…”
Section: Discussionsupporting
confidence: 86%
“…The signaling pathway by which the status of the developing chloroplast is relayed to the nucleus is one of the few remaining plant signaling pathways that we know of, but for which we have little idea of the signaling components involved. We believe this study resolves one of the major discrepancies in plastid signaling research by eliminating a major role for PTM, and paves the way for more focused studies that build on recent progress on the role of tetrapyrroles and chloroplast protein homeostasis in plastid retrograde signaling (Woodson et al, 2011;Maruta et al, 2015;Ibata et al, 2016;Tadini et al, 2016).…”
mentioning
confidence: 66%
“…In this study, gene expression analysis showed that the lpe2 mutation generated a retrograde signal, thus altering the expression of several different kinds of genes (Figure 4), including those involved in C and N response ( Figure 5). Since the expression of C and N response genes is regulated by C/N balance (Oliveira and Coruzzi 1999;Martin et al 2002;Maruta et al 2015), our data suggest that LPE2 is also involved in C/N balance. This was supported by the C/N stress test, in which the loss of LPE2 suppressed C/N response ( Figure 6).…”
Section: Discussionmentioning
confidence: 75%